Peak condition - Garrick, J. G., Radetsky, P. (New York Croun Publishers, 1986)
Garrick, a physician and director of the Center for Sports Medicine in San Francisco, and medical writer Radetsky have written a superb reference guide to sports and exercise injuries. A chatty but authoritative narrative explains body structure and function, what injuries occur most frequently during exercise and sports, how to recognize which injuries require medical attention and how to treat some problems at home. Each chapter begins with an office visit to Garrick by a weekend or professional athlete who has sustained an injury. Garricks expertise as well as his empathy with his patients adds to the confidence that the reader quickly develops in his suggestions. The chapters in the first half of the book are divided into discussions of body parts (ankle, foot, knee, etc.) that are subdivided by specific injuries, with accompanying detailed illustrations of trouble spots and ""what to do instructions. The second half of the book enumerates specific sports and exercises, with advice ranging from how much time should be spent in an aerobics class for maximum benefit to preventing sunburn while skiing.
Keywords: Science